Moisture, fat content and fatty acid composition in breaded and nonbreaded deep-fried black pomfret (Parastromateus niger) fillets - Moradi, Yazdan; Bakar, Jamilah; Che Man, Yaakob; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Effects of breading materials and deep-fat frying on fat uptake, moisture content and fatty acid composition of the black pomfret (Parastromateus niger) fillets. Black pomfret fillets both breaded and non-breaded were deep-fat fried in sunflower oil and palm olein. Fat uptake, moisture content and fatty acid composition in the fillets were determined. Total fat content in the fillets of both breaded and un-breaded fillets increased significantly (p<0.05); approximately 10 times in the non-breaded fillets and less than twice in the breaded fillets. Saturated fatty acids (SFA) of raw fillets significantly (P<0.05) decreased when fried in sunflower oil. However, it slightly increased during deep-frying in palm olein. A significant (P<0.05) increase in the monounsaturated fatty acids (MUFA) was observed in both oils fried samples. The amount of polyunsaturated fatty acids (PUFA) increased in sunflower oil fried fillets and decreased in palm olein fried ones. The n-6/n-3 ratios were observed to increase in both sunflower oil and palm olein fried fillets. The increases were significantly (P<0.05) less in breaded than those in the non-breaded fillets. Breaded fillets had lower changes in the fatty acid composition than non-breaded fillets.